Rural energy for sustainable development technology and environmental issues - Chaturvedi, Pradeep; Indian Association for the Advancement of Science (New Delhi : Concept Pub. Co., for Indian Association for the Advancement of Science, 1998)
Deals indepth with the biomass production and requirement in South Asia, with special reference to India.
Includes bibliographical references and index.
Keywords: Renewable energy sources -- South Asia; Rural development -- South Asia; Environmental protection -- South Asia